2022
DOI: 10.1001/jama.2021.24751
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Plasma Injections vs Placebo for Patients With Ankle Osteoarthritis

Abstract: HCV testing, and 10.7% (n = 188) offered HCV treatment. Among non-OTPs in 2020, 46.6% (n = 3024) offered HIV testing, 17.9% (n = 1163) offered HIV treatment, 45.8% (n = 2976) offered HCV testing, and 20.5% (n = 1334) offered HCV treatment.For both OTPs and non-OTPs, HIV and HCV testing and treatment were most often available in federally owned facilities and facilities with inpatient services, with the proportion of outpatient-only facilities providing such services being low (Table 2).Of the 117 OTPs in the 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The current systematic review by Paget et al [10] follows a recent, prominent randomized controlled trial by many of the same authors, who found no benefit to platelet-rich plasma (PRP) injections compared with saline placebo [11]. That report generated numerous letters to the editor, including several from officers of regenerative medicine centers and consultants for manufacturers of PRP harvest systems [3, 6]. The legitimate concern raised in these responses, as well as responses to similar negative results for injections in the knee [4], is that a clear consensus about the optimal formulation of most injected substances does not exist, particularly for PRP.…”
Section: Where Are We Now?mentioning
confidence: 99%
“…The current systematic review by Paget et al [10] follows a recent, prominent randomized controlled trial by many of the same authors, who found no benefit to platelet-rich plasma (PRP) injections compared with saline placebo [11]. That report generated numerous letters to the editor, including several from officers of regenerative medicine centers and consultants for manufacturers of PRP harvest systems [3, 6]. The legitimate concern raised in these responses, as well as responses to similar negative results for injections in the knee [4], is that a clear consensus about the optimal formulation of most injected substances does not exist, particularly for PRP.…”
Section: Where Are We Now?mentioning
confidence: 99%
“…The trials found that intra-articular PRP injections did not induce a significant difference in symptoms, structure, or function in the ankle or knee when compared with placebo injections 9,10 . The results from these studies, however, were met with concerns, most of which focused on the fact that the PRP preparation protocol was not one that is standardly used in clinic, thereby raising concerns about insufficient platelet numbers 11,12 . Despite the many concerns raised, one question remained both unasked and unanswered : Do the patient characteristics play a role in the efficacy of PRP?…”
mentioning
confidence: 99%